Assessment of Sectoral Virtual Water Flows and Future Water Requirement in Agriculture Under SSP-RCP Scenarios: Reflections for Water Resources Management in Zhangye City - Wang, Yifei; Wu, Haowei; Li, Zhihui (Frontiers in Ecology and Evolution, 2022)
Water scarcity is a core issue that constraints high-quality development of arid areas in the northwest of China. Zhangye is an oasis city that located in the Heihe River Basin in the northwestern China. It is with an agriculture-dominated economy and facing more and more serious water crisis. Virtual water is an indicator that can measure the embodied water in the traded products, which has been widely applied for making rational policies for water resources management. In addition, clarifying water requirement in agricultural sectors under future climate change scenarios is essential to develop more appropriate adaptation strategies. From this perspective, this study aims to evaluate and compare virtual water flows among various sectors in Zhangye of year 2012 and 2017 with a single regional input-output model and further to clarify the future water requirement tendency in agriculture during 2020-2050 under different SSP-RCP scenarios. The results showed that planting sector directly contributed most of total water consumption with the highest direct coefficient of 3307.5 m3/yuan in 2012, while manufacture of food products and tobacco processing sector had the largest proportion of indirect water consumption (99%) mainly from intermediate inputs of agricultural products. Water consumption intensity of all sectors averagely decreased by 22% during 2012-2017, indicating an increasing water utilization efficiency in economic industries. Household consumption also can improve water utilization efficiency as the major path for final consumption (86.4% in 2017). Water scarcity of Zhangye was becoming increasingly prominent since virtual water net exports were higher than local consumption especially in agriculture, manufacturing, and energy supply industries. Moreover, under climate change scenarios, we found the highest level of water requirement per unit area occurred in 2000, but it still had an incremental potential by 2050, especially in SSP585. The high requirement intensity and large-scale maize planting caused a rising tendency of total crop water requirement with an annual increasing rate of 8.4% from 1980 to 2050. This makes it possible to adapt climate change through scientific management measures and technical means. We further made policy implications for adaptive management of water resources in Zhangye.